The Key to Success and Challenges of Bali's Women Entrepreneurs - Ni Luh Indah Sukma Pertiwi; Luh Putu Mahyuni (PT. Publikasiku Academic Solution, 2024)
This study examines the key to success & business development strategies that can influence the success of Balinese women entrepreneurs with the challenges they face. The purpose of this study is to determine the factors that are the key to success, the development strategies used and what challenges Balinese women face in running their businesses. The type of research that will be used in this study is a qualitative approach. The data collection techniques used are interviews and observations. The determination of informants in this study used 9 informants as Balinese women who came from different districts with married status but had different types of businesses and who did not work tied to the company. Data analysis in this study is data reduction, data display, and data conclusion drawing/verification. The results of the study show that the key to success is innovation and creativity, motivation, having self-efficacy, work life balance and family support. Strategies in developing a business are market development strategies and innovation strategies. The challenges faced by women entrepreneurs in running a business are in expanding the network. Apart from that, to run a business you also have to be smart in managing your time between business and household obligations as well as traditional activities such as menyama braya or other traditional ceremonies so that everything runs in balance.